206k views
3 votes
Please hurry! If you don't know it, that's okay.

What is the solution to the system of equations below?

y = 2/5 x - 3 and x = –10

(–10, –7)

(–10, –1)

(–7, –10)

(–1, –10)

User AMDI
by
6.3k points

2 Answers

4 votes

Answer:

A

Explanation:

User Lahiru Pinto
by
5.4k points
4 votes

Answer:

The answer is (x,y)=(-10,-7)

Explanation:

  • The solution comes from replace x= -10 into the equation of y=2/5 x -3.
  • Replacement of x= -10 into y = 2/5 x -3 results:
    y=(2)/(5)*{(-10)}-3=2*{(-2)} -3=-4-3=-7.
User Fredrik Frodlund
by
5.9k points